Overview and Analysis of the Cost of Drug Programs in Poland: Public Payer Expenditures and Coverage of Cancer and Non-Neoplastic Diseases Related Drug Therapies from 2015–2018 Years - Mela, Aneta; Poniatowski, Łukasz A.; Drop, Bartłomiej; Furtak-Niczyporuk, Marzena; Jaroszyński, Janusz; Wrona, Witold; Staniszewska, Anna; Dąbrowski, Jan; Czajka, Anna; Jagielska, Beata; Wojciechowska, Monika; Niewada, Maciej (Frontiers in Pharmacology, 2020)
Background: In Poland drug programmes developed by the Minister of Health and financed by National Health Fund are special reimbursement framework of innovative, expensive and mostly hospital medical products used for a small number of patients. Research design: The research presented in this paper was based on analysis of data published by the National Health Fund in Poland. The analysis focused on estimating public payer expenditure on drugs available within drug programmes in years 2015-2018. Results: In subsequent years reimbursement of drugs used within drug programmes was associated with the National Health Fund budget expenditure of 635 mln USD, 755 mln USD 854 mln USD and 921 mln USD, respectively. Oncology drug programmes reimbursement constituted 48.1%, 42.5%, 47.1%, 52.4 and were approx. 305, 312, 402, 483 mln USD whereas values of non-oncology drug programmes were approx. 330, 434, 452, 438 mln USD and constituted 51.9, 57.5%, 52.9%, 47.6% respectively. Conclusions: Number of drug programmes increased from 69 in 2015 to 92 in 2018 covering more than 100 active substances. Increase was driven mainly by oncology programmes.